Antimicrobial Peptide from the Eusocial Bee Halictus sexcinctus Interacting with Model Membranes. Issue 5 (11th July 2012) - Pazderková Pazderková, Markéta Markéta; Kočišová Kočišová, Eva Eva; Pazderka Pazderka, Tomáš Tomáš; Maloň Maloň, Petr Petr; Kopecký Jr. Kopecký Jr., Vladimír Vladimír; Monincová Monincová, Lenka Lenka; Čeřovský Čeřovský, Václav Václav; Bednárová Bednárová, Lucie Lucie
Abstract : Halictine-1 (Hal-1)—a linear antibacterial dodecapeptide isolated from the venom of the eusocial bee Halictus sexcinctus —has been subjected to a detailed spectroscopic study including circular dichroism, fluorescence, and vibrational spectroscopy. We investigated Hal-1 ability to adopt an amphipathic α -helical structure upon interaction with model lipid-based bacterial membranes (phosphatidylcholine/phosphatidylglycerol-based large unilamellar vesicles and sodium dodecylsulfate micelles) and helix inducing components (trifluoroethanol). It was found that Hal-1 responds sensitively to the composition of the membrane model and to the peptide/lipid ratio. The amphipathic nature of the helical Hal-1 seems to favour flat charged surfaces of the model lipid particles over the nondirectional interaction with trifluoroethanol. Increasing fraction of polyproline II type conformation was detected at low peptide/lipid ratios.